Diet of Gastritis Patients in Beka Village - Andi Nur Indah Sari; Fanny Metungku; Niswa Salamung; Chely Veronica Mauruh (D'Nursing and Health Journal (DNHJ), 2021)
Introduction: Globally, Indonesia ranks fourth with the highest number of gastritis sufferers. The most common cause is an infection with the Helicobacter pylori bacteria which causes inflammation of the stomach. One of the causes of this ganstritis is a poor diet. The aim of this research is to know the diet of gastritis patients in Beka village. Method: This type of research is descriptive research. The population in this study were all 35 gastritis sufferers in Beka Village. The sample in this study was the entire population used as a sample in Beka Village, amounting to 35 people. The sampling method was non-probability sampling with a total sampling approach model. Result:The results showed that of the 35 respondents, 60% of the food patterns were good and 40% less good. It is hoped that gastritis patients can improve their diet so that they can reduce the recurrence of the disease. Conclusion: more gastritis patients have a bad diet. It is hoped that gastritis patients can improve their diet for the better so that it can reduce disease recurrence and complaints experienced by patients.